Integrating Ardhanarishwar Symbolism and Bisexuality: A Neurotherapy Based Approach to Alleviating Back Pain through Alternative Healing - Jatin, Jatin; Yadav, Snehlata; Gopal Dixit, Guru Acharya Ram; Kumar, Sunil; Rathi, Jyoti (Journal of Neonatal Surgery, 2025)
The deity Ardhanarisvara is a representation of Shiva as both male and female, where "Ardha" signifies "half" and "Nari" means "woman." This iconic form underscores the inherent unity of Shiva and his Shakti, Parvati, emphasizing that Shiva is incomplete without his feminine counterpart. Ardhanarisvara embodies the philosophical concept of the interconnectedness and equal importance of Purusha (masculine principle, consciousness) and Prakriti (feminine principle, nature/matter/energy). This symbolic duality is mirrored in human biology. Human development is not strictly unisexual; rather, each individual possesses the inherent capacity for both male and female characteristics. In fetal development, both Mullerian and Wolffian ducts are present. The Mullerian duct differentiates into female internal reproductive organs (fallopian tubes and uterus), while the Wolffian duct develops into male internal reproductive organs (epididymis, vas deferens, and male external genitalia). The hormonal balance of testosterone and estrogen, both present in the fetus, plays a crucial role in determining sexual differentiation. Anatomically, the human spine is segmented into five distinct regions: cervical, thoracic, lumbar, sacral, and coccygeal. Certain holistic health perspectives propose a link between energy centers, such as the "Nabhi" and chakras, with organ function and potentially musculoskeletal issues like back pain. Back pain encompasses various classifications including lumbosacral, radicular, and referred pain, often attributed to pathologies like disc bulge, herniation, or degeneration. These conditions are broadly categorized as Non-Specific Low Back Pain or Specific Low Back Pain. Wellness Neurotherapy aims to address these conditions through treatment protocols tailored to individual patient history, present clinical presentation, and diagnostic assessments.